PARTISIPASI IBU RUMAH TANGGA ANGGOTA PKK PROGRAM PANGAN TERHADAP KETAHANAN PANGAN RUMAH TANGGA DI DESA NGANDONG KECAMATAN GANTIWARNO KABUPATEN KLATEN - Septiana, Dikri; Maharani, Artita Devi; Ratri, Wahyu Setya (Fakultas Pertanian UST, 2024)
This research aims to analyze the participation of housewives in the PKK activities of the Ngandong Village food program and the influence of the participation of housewives as members of the PKK food program on the level of food security of Ngandong Village households. The basic method used is a quantitative descriptive method. The sampling method used a census, namely all 40 PKK members. The data analysis method uses simple linear regression. The research results show that 1) Participation of housewives who are members of the PKK in planning, implementation, monitoring and evaluation as well as utilization of food program results is relatively high, namely in the interval 481- 640. 2) The level of household food security in Ngandong Village is included in the food secure category because the share of food expenditure is less than 60%.